PACMAN NEW GENERATION: SEBUAH TRANSFORMASI NEGOSIASI? PEMULIHAN CITRA KOMUNITAS SUPORTER DALAM DINAMIKA LINGKUNGAN MADRASAH - Nugraha, Muhammad Bintang; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2026)
This article aims to uncover the strategies used by the Pacman Mansda supporter community at MAN Sidoarjo to build a positive image. This effort was carried out in response to negative stereotypes that accused the group of being undisciplined and significantly disrupting school order. Using a qualitative case study design involving Pacman Mansda administrators and members as the main subjects. Data were collected through interviews, observations, and documentation, then analyzed using systematic data reduction, presentation, and conclusion drawing. The results of the study indicate that the Pacman Mansda community uses image repair strategies carried out by individual members and the community collective. Pacman adopted three of the five strategies of Benoit's Image Repair Theory: (1) corrective action, (2) reducing offensiveness, and (3) evasion of responsibility. Denial and mortification strategies were not implemented, which was due to the consequences of the unequal power relations between teachers and students in the educational environment. Evidence shows that the school believes more in concrete actions than in apologies. The conclusion confirms that real behavioral transformation and proactive involvement in positive school activities are the most effective strategies in reconstructing the community image to be more constructive and acceptable.